Analisis Kerusakan Perkerasan Dengan Metode Surface Distress Index (SDI) Dan Perencanaan Perbaikan Jalan (Studi Kasus: Ruas Jalan Sidas - Simpang Tiga) - Wiro Wiro; Komala Erwan; Siti Nurlaily Kadarini (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2022)
ABSTRACTOne of the provincial roads in West Kalimantan is the Sidas – Simpang Tiga Road in Landak Regency. Some of these road segments experienced moderate to light damage, this road damage caused several consequences including road damage causing loss of comfort for road users, road damage always triggers accidents, road damage is very disturbing to road users such as passenger buses, trucks transporting agricultural products and plantations and other road users who cross this road. The purpose of this study was to determine the level of road damage that occurred. The method used in this study is the Surface Distress Index (SDI) method. From the results of the study, it was found that a total of 27 road segments were collected with data with a total area of 11820.00 m2, crack damage was 15.56%, pothole damage was 1.57% and wheel rut damage was 0.47%. The results of the analysis stated that the level of damage that was classified as lightly damaged occurred in segments 3, 4, 7, 8, 10, 15, 17, 19 and 24. Severely damaged conditions occurred in segment 21 and other segments were in moderate condition.Keywords: Road Damage, Surface Distress Index (SDI).